2016
DOI: 10.1038/bmt.2015.347
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival polyploid cells and donor-derived myofibroblasts in ocular GvHD

Abstract: After allogeneic hematopoietic stem cell transplantation (allo-SCT), ocular GvHD is a common complication, typical symptoms being dry eye syndrome with features of fibrosis. In this study, we have identified and quantified two cell types-myofibroblasts (MFB) and polyploid (PP) cells-in the conjunctival surface of allo-SCT patients (pts) and have explored their kinetics and association with local and systemic GvHD. Results are compared with control groups of (a) pretransplant samples from allo-SCT patients, (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Three studies were found describing BMDCs in the conjunctiva of humans with ocular grafts versus host disease [ 101 , 102 , 103 ]. All three employed sex-mismatch lineage tracing and found that BMDCs contributed to (myo)fibroblasts in the conjunctiva.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were found describing BMDCs in the conjunctiva of humans with ocular grafts versus host disease [ 101 , 102 , 103 ]. All three employed sex-mismatch lineage tracing and found that BMDCs contributed to (myo)fibroblasts in the conjunctiva.…”
Section: Resultsmentioning
confidence: 99%
“…Donor-derived endothelial cells and myofibroblasts were found to constitute around 5.4% of all cells with no clear relation with time since transplantation. Hallberg et al performed two studies for which the first [ 103 ] 17 samples from nine patients were collected, whereas the second [ 102 ] included 70 samples from 46 patients. In both studies, approximately 9% of myofibroblasts were determined to be of donor origin, which increased gradually over time.…”
Section: Resultsmentioning
confidence: 99%
“…Conjunctival subepithelial fibrosis also referred to as subtarsal fibrosis, is present in 50% of patients with ocular GVHD but is absent in all non-GVHD moderate or severe DED patients. Animal studies have also shown that GVHD-associated conjunctival fibrosis is accompanied by donor-derived myofibroblast formation and Ras system activation (72)(73)(74). Additionally, there was marked infiltration of neutrophils at the upper palpebral conjunctiva in patients with ocular GVHD, which might be associated with the clinical manifestations and inflammatory status of the ocular surface.…”
Section: Conjunctival Involvementmentioning
confidence: 97%
“…One Swedish study examined conjunctival specimens of 25 females with male donor recipients and found the ratio of donor myofibroblasts to total myofibroblasts correlated with coGVHD severity. Additionally, the ratio of donor myofibroblasts (XY) to recipient myofibroblasts increased with time post‐transplant 49 . Donor fibroblasts and subsequent fibrosis also contribute to signs of tear dysfunction and abnormal anatomy in coGVHD.…”
Section: Gvhd Histology and Pathophysiologymentioning
confidence: 99%
“…Additionally, the ratio of donor myofibroblasts (XY) to recipient myofibroblasts increased with time posttransplant. 49 Donor fibroblasts and subsequent fibrosis also contribute to signs of tear dysfunction and abnormal anatomy in coGVHD.…”
Section: The Conjunctiva: Acute Ogvhd Cogvhd and Dedmentioning
confidence: 99%